The Argasidae, Ixodidae and Nuttalliellidae (Acari: Ixodida) of the world: a list of valid species names - Guglielmone, Alberto Alejandro (2010)
This work is intended as a consensus list of valid tick names, following recent revisionary studies, wherein we recognize 896 species of ticks in 3 families. The Nuttalliellidae is monotypic, containing the single entity Nuttalliella namaqua. The Argasidae consists of 193 species, but there is widespread disagreement concerning the genera in this family, and fully 133 argasids will have to be further studied before any consensus can be reached on the issue of genus-level classification. The Ixodidae comprises 702 species in 14 genera: Amblyomma (130 species, of which 17 were formerly included in Aponomma, a genus that is still considered valid by some authors), Anomalohimalaya (3), Bothriocroton (7, all previously included in Aponomma), Cosmiomma (1), Cornupalpatum (1), Compluriscutula (1), Dermacentor (34, including the single member of the former genus Anocentor, which is still considered valid by some authors), Haemaphysalis (166), Hyalomma (27), Ixodes (243), Margaropus (3), Nosomma (2), Rhipicentor (2) and Rhipicephalus (82, including 5 species from the former genus Boophilus, which is still considered valid by some authors). We regard six names as invalid: Amblyomma laticaudae Warburton, 1933 is a synonym of Amblyomma nitidum Hirst & Hirst, 1910; Bothriocroton decorosum (Koch, 1867) is a synonym of B. undatum (Fabricius, 1775); Haemaphysalis vietnamensis Hoogstraal & Wilson, 1966 is a synonym of H. colasbelcouri (Santos Dias, 1958); Haemaphysalis xinjiangensis Teng, 1980 is a synonym of H. danieli Č erný & Hoogstraal, 1977; Hyalomma erythraeum Tonelli-Rondelli, 1932 is a synonym of H. impeltatum Schulze and Schlottke, 1930 and Rhipicephalus hoogstraali Kolonin, 2009 was not described according to the rules of the International Code of Zoological Nomenclature.